Sobre pavimentações do plano euclidiano - Silva, Rafael Necchi [UNESP] (2014)
This work has the purpose to develop and assist the study about tessellations in Euclidean Plane, showing various types of paving and some applications. We analyze some classes of convex polygons and not convex so we can better understand why they are or not acceptable in paving. The central objective in this work is the application the study of paving in the classroom, where it is shown different ways to learning at different ages